PENGUATAN GENDER DALAM PENDIDIKAN ISLAM - Supriyadi, Ahmad Rizal; Darma, Ade; Mutaqin, Mumu Zainal; Arifin, Muhammad (Institut Agama Islam Sahid (INAIS) Bogor, 2025)
Gender issues have been a continuous topic of discussion from the era of Jahiliyyah until today. The idea of gender equality in education has become increasingly important to be studied, resolved, and implemented in both educational institutions and society. For thousands of years, discriminatory practices against women have created a doctrine that women should not be involved in economic, political, religious, or educational spheres. This social inequality has led to limited access for women to formal education and an increase in gender-based violence. In Islamic teachings, however, women are highly respected and honored, even though certain boundaries are set by religion. This study uses a library research method by collecting various literatures related to the strengthening of gender roles in Islamic education. The findings show that gender empowerment in Islamic education today can be seen through the increasing access of women to education, the development of gender-responsive curricula, the emergence of female scholars and academics, supportive government and institutional policies, and Islamic character education that emphasizes justice and equality. The study concludes that Islamic education is currently moving toward justice and gender equality while maintaining the fundamental Islamic values that uphold morality and spirituality in human life.